2021
DOI: 10.1089/rej.2021.0025
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Gut Microbiome Remodeled During Intermittent Fasting in Humans

Abstract: Intermittent fasting (IF) is the practice of restricting food intake for 12-48 hours per fasting cycle over a prolonged period of time. Previous study shows beneficial health effects such as weight loss and lower risk for cardiometabolic diseases. Although reduced calorie intake may account for some of the observed benefits of IF, exact mechanisms are still unclear. Recent evidence indicates that IF may lead to remodeling and increased taxonomic diversity in the human gut microbiome. In particular, the Lachnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The current study also found FI students to have an increased abundance of family Enterobacteriaceae . Bacteria belonging to family Lachnospiraceae ferment plant polysaccharides into SCFAs and alcohols but also are able to degrade mucin, which may be advantageous during periods of energy deprivation 40 , such as with food insecurity. Conversely, Enterobacteriaceae is a bacterial family that includes numerous pathogenic bacteria such as Salmonella and Escherichia coli , but also primarily consists of facultative anaerobes that ferment glucose 41 .…”
Section: Discussionmentioning
confidence: 99%
“…The current study also found FI students to have an increased abundance of family Enterobacteriaceae . Bacteria belonging to family Lachnospiraceae ferment plant polysaccharides into SCFAs and alcohols but also are able to degrade mucin, which may be advantageous during periods of energy deprivation 40 , such as with food insecurity. Conversely, Enterobacteriaceae is a bacterial family that includes numerous pathogenic bacteria such as Salmonella and Escherichia coli , but also primarily consists of facultative anaerobes that ferment glucose 41 .…”
Section: Discussionmentioning
confidence: 99%
“…One identified species Lachnospiraceae bacterium 3 1 57FAA CT1 belonged to Lachnospiraceae which is involved in the production of short-chain fatty acid (SCFA) through fermenting plant polysaccharides [ 37 , 38 ]. In addition, Lachnospiraceae bacterium 3 1 57FAA CT1 has phylogenetic similarity to known butyrogenic gut bacteria [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…IF was more advantageous in improving intestinal immunity, increasing the expression of the intestinal nuclear transcription factor‐kappa B (NF‐κB) inhibitor IKB, and decreasing circulating immune factors. In addition, several studies have demonstrated that fasting‐induced gut microbiota remodeling is also involved in regulating energy metabolism, adipose tissue browning, and the brain–gut–microbiome signaling axis 305–307 . Liu et al 308 .…”
Section: Potential Mechanism Mediating the Effects Of Dietary Patternsmentioning
confidence: 99%
“…In addition, several studies have demonstrated that fasting-induced gut microbiota remodeling is also involved in regulating energy metabolism, adipose tissue browning, and the brain-gut-microbiome signaling axis. [305][306][307] Liu et al 308 demonstrated that ADF improved cognitive performance in diabetic mice by remodeling the microbiota composition, increasing the content of micro-bial metabolites butyrate, acetate, and short-chain fatty acids (SCFAs), and regulating insulin signaling and brainderived neurotrophic factor expression. Another study also demonstrated that fasting-induced changes in the functional aspect of gut microbiota improved BP control and metabolism by affecting SCFA production.…”
Section: Gut Microbiota and Its Metabolitesmentioning
confidence: 99%